The Moderating Role of Non-Financial Compensation in the Relationship Between Job Satisfaction, Motivation, Work Environment, and Employee Performance in Public Health Centers in Surabaya - Nurmalasari, Yulia; Harsono, Soni; Sari, Linda Purnama (Universitas Muhammadiyah Pontianak, 2025)
This study aims to evaluate the impact of satisfaction, motivation, and work environment on employee performance, with non-financial compensation as a moderating variable. This study was conducted at a Public Health Center (Puskesmas) in Surabaya, involving 206 employees selected using a purposive sampling method. The collected data were analyzed using SEM PLS through Smart PLS 4. The findings of this study indicate that motivation and work environment have a positive significant influence on employee performance. Moderation analysis shows that non-financial compensation strengthens the influence of job satisfaction on employee performance. It is recommended that the integration of non-financial compensation in human resource management policies be used as a sustainable approach to improve employee performance in public health institutions.